Two new species of Spathiphyllum (Araceae) from Tabasco, Mexico with notes on their floral scent - Díaz Jiménez, Pedro; Dötterl, Stefan; Fuchs, Roman; Hentrich, Heiko; Pérez-Farrera, Miguel Ángel; Padilla Vega, José; Aguilar-Rodríguez, Pedro A. (Phytotaxa, 2022)
In Mexico, the mostly neotropical genus Spathiphyllum is represented by twelve species, including only one species for the state of Tabasco. A detailed review of herbarium specimens, and material collected and cultivated from different locations in Tabasco, allowed us to conclude that S. cochlearispathum does not occur in Tabasco, and that specimens from different populations identified as S. cochlearispathum correspond to two different species. Here, we describe and illustrate S. maldonadianum and S. wilfridianum, two new species from Tabasco, Mexico, one of which is critically endangered. We also provide data on the composition of the floral scent of both species and their phenology.